2012
DOI: 10.1177/0310057x1204000313
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Thrombotic Tendency of Reactive Thrombocytosis in Critically Ill Patients: A Prospective Case-control Study

Abstract: It is uncertain whether reactive thrombocytosis is associated with an increased risk of thrombosis. This prospective case-control study assessed the in vitro thrombotic tendency of patients with reactive thrombocytosis. Forty-eight patients with reactive thrombocytosis, defined by platelet count >500×10 9 /l and 55 similar, randomly selected critically ill patients who did not have reactive thrombocytosis were considered. In vitro thrombotic tendency in both groups of patients was assessed using the maximal am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…Second, our results confirmed the increasing recognition of the importance of platelets and fibrinogen in the pathogenesis of critical bleeding, haemostasis and thrombosis (Duff et al, ; Ho et al, ; Hagemo et al, ). Our multivariate analysis results showed that fibrinogen concentrations and platelet counts certainly had a larger effect on in vitro clot strength than hypocalcaemia.…”
Section: Discussionsupporting
confidence: 88%
“…Second, our results confirmed the increasing recognition of the importance of platelets and fibrinogen in the pathogenesis of critical bleeding, haemostasis and thrombosis (Duff et al, ; Ho et al, ; Hagemo et al, ). Our multivariate analysis results showed that fibrinogen concentrations and platelet counts certainly had a larger effect on in vitro clot strength than hypocalcaemia.…”
Section: Discussionsupporting
confidence: 88%
“…In a prospective study of 147 splenectomy patients over a median period of 23 months, 14.3% of the patients with severe reactive thrombocytosis (> 650 × 10 9 L −1 ) without myeloproliferative diseases developed portal, mesenteric or splenic vein thrombosis compared with no VTE events among those without severe reactive thrombocytosis [23]. Our recent study also showed that reactive thrombocytosis in critically ill patients was associated with an increased in vitro thrombotic tendency and platelet counts had a relatively linear ‘dose‐related’ relationship with the strength of thrombotic tendency when measured by a thromboelastograph (Pearson’s correlation coefficient = 0.53, P < 0.001) [15]. This ‘dose‐related’ in vitro thrombotic tendency of reactive thrombosis is indeed consistent with the findings of this study – the risk of VTE is linearly related to the platelet counts when platelet counts are > 400 × 10 9 L −1 .…”
Section: Discussionmentioning
confidence: 96%
“…In this study, reactive thrombocytosis was defined as platelet count ‡ 500 · 10 9 L )1 [15]. The sample size was estimated to have 90% power if the incidence of VTE of patients without reactive thrombocytosis was 3%, incidence of reactive thrombocytosis was 20% and its associated relative risk of VTE was three.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a scatter plot is pivotal when Pearson's or Spearman's correlation coefficient is used because it allows us to visualise whether the relationship between the two variables is linear, bimodal U shape, sigmoidal or quadratic 2 . Pearson's product-moment correlation coefficient should be reserved for situations when assessment of the degree of linearity between two continuous variables is intended 3 . Other forms of regression may be more appropriate when the relationship between two variables is not linear 4 .…”
Section: A Scatter Plot Is Essential To Interpret Correlation Coefficmentioning
confidence: 99%